Financial Integration and Economic Growth in Europe - Guglielmo Maria Caporale; Anamaria Diana Sova; Robert Sova (Center for Economic Studies and ifo Institute (CESifo), 2023)
This study examines the impact of financial integration on economic growth in the case of 31 European countries over the period from 2000 to 2021 using dynamic panel data models. The estimation results provide evidence of significant positive effects of financial integration on economic growth. They also suggest that the financial integration – economic growth relationship depends on country-specific characteristics such as the level of financial development and the quality of institutions. More precisely, financial integration appears to exert a greater positive influence on growth in the case of the European countries with a higher level of financial development and better institutions.
Keywords: C33; F36; 330; financial integration; economic growth; Europe; financial development; quality of institutions; dynamic panel models; GMM estimator